Analysis of the factors contributing to the degradation of coral reefs and marine biota at Pasir Putih Beach, Prigi Bay, Trenggalek District, East Java, Indonesia - RAHMANTA SETIAHADI; MARHENY LUKITASARI; NURUL KUSUMA DEWI; SUMANI SUMANI; CATUR RETNANINGDYAH; MUKHTASOR MUKHTASOR (Society for Indonesian Biodiversity, 2025)
Abstract. Setiahadi R, Lukitasari M, Dewi NK, Sumani, Retnaningdyah C, Mukhtasor. 2025. Analysis of the factors contributing to the degradation of coral reefs and marine biota at Pasir Putih Beach, Prigi Bay, Trenggalek District, East Java, Indonesia. Biodiversitas 26: 1384-1394. The deterioration of coral reefs and marine ecosystems poses a significant challenge that needs to be addressed to maintain sustainable marine ecotourism management. Both natural processes and human activities contribute to the decline of coral reef ecosystems. This study seeks to examine the factors causing damage to coral reefs and marine life along the Karanggongso Coast, East Java Province, Indonesia. The research utilized a survey method combined with a descriptive analytical approach. Coral reef surveys were conducted using the Line Intersept Transect (LIT) technique, while sedimentation and land cover changes were assessed using grab samplers, Google Earth maps, and Rupa Bumi Indonesia (RBI) maps. Beach physical condition observations provided material for descriptive analysis, and coral reef and sedimentation data were used to create indicative maps. The overlay of indicative maps and descriptive analysis results were employed in the spatial analysis of factors destroying coastal ecosystems. The study findings revealed the Physical Condition of the Waters, with indicators including temperature (28.7oC), salinity (35%), dissolved oxygen (13.2 Ppm), pH (7.73), and brightness (4.5m). While these conditions remain favorable, extensive sedimentation has reduced the Percentage of Coral Reef Cover to below 24.9%. Analysis of sedimentation from land use change indicates that significant areas of forest and shrubland have been converted to agricultural land, settlements, tourist facilities, and several shrimp ponds, leading to erosion and sedimentation. The size of the sediment grains in the water reflects the predominant sand content at each station, with values ranging from 99.19% to 99.63%.